(untitled) (LACCEI, 2024)
This paper presents applications of Geoengineering tools such as a Geographic Information System (GIS) and a 2D mathematical modeling program on the Malvinas plateau and the North Scotia ridge. Due to the important tectonic activity at the edges of the Scotia, South American and Sandwich plates with the possibility of producing important variations in sea height or tsunamis, it is very important to characterize the crust in the area for the prevention of economic losses in port areas. In this work, freely accessible geological, geophysical, gravimetric and ocean depth data and a compilation of sedimentary thicknesses from the Institute of Applied Geodesy and Geophysics of the Faculty of Engineering of the University of Buenos Aires were used. From the application of the GIS it was possible to map the areas at risk and calculate the distances between the points of possible ruptures of the crust and the urban centers such as Puerto Argentino or the nearby Antarctic Bases of the region. On the other hand, the application allows to highlight areas of cortical weakness by applying geospatial filters in the frequency domain on gravimetric data and thus expand the areas of prevention. The 2D gravity modeling allowed to locate new zones of weakness, showing their extension and depth in a profile that crosses the North Scotia Ridge. Keywords - GIS, 2D modeling, earthquakes, faults.